Psychophysiological Responsivity to Script-Driven Imagery: An Exploratory Study of the Effects of Eye Movements on Public Speaking Flashforwards - Kearns, Michelle; Engelhard, Iris M. (Frontiers in Psychiatry, 2015)
A principle characteristic of public speaking anxiety relates to intrusive mental images of potential future disasters. Previous research has found that the self-reported emotionality of such “flashforwards” can be reduced by a cognitively demanding, dual-task (e.g., making eye movements) performed whilst holding the mental image in mind. The outcome measure in these earlier studies was participants’ self-reported emotional intensity of the mental image. The current study (N=34) explored whether an objective measure of emotionality would yield similar results in students with public speaking anxiety. A script-driven imagery procedure was used to measure psychophysiological responsivity to an audio script depicting a feared (public speaking) scenario before and after an eye movement intervention. Relative to the control condition (imagery only), those who made eye movements whilst holding a mental image of this scenario in-mind demonstrated a significant decrease in heart rate, which acted as a measure of emotionality. These findings add to a previous body of research demonstrating the beneficial qualities of eye movements and their potential for treatment of both past and future-oriented anxieties.